ANALISIS SISTEM DAN PROSEDUR MANAJEMEN PERSEDIAAN OBAT DI RUMAH SAKIT - Noor Muhammad Adipati; Efa Wahyuni (Jurnal Aplikasi Perpajakan, 2025)
The purpose of this research is to get a comprehensive picture of the system and procedures for the current medicine inventory management at XYZ Hospital. Then provide a redesign of the Medicine Inventory management system and procedures at XYZ Hospital. The method used in this research is a qualitative method with a descriptive approach. This research was conducted by interview, observation and documentation with the parties involved in the application of medicine supply management systems and procedures at XYZ Hospital. Based on the results of the study, the drug supply management system and procedures at XYZ Hospital as a whole are still less effective. This is because the ongoing systems and procedures do not meet the standard criteria according to the COSO Internal Control Framework internal control system. several weaknesses that need to be improved, such as (1) The existence of multiple functions in one section, so that there is a duality of authority and responsibility for employees. (2) The existence of system recording activities and drug inventory management procedures are still carried out manually. (3) Documents that still do not meet the system and procedures for drug supply management.